2020
DOI: 10.3389/fbioe.2020.599560
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Microbial Isoprenoid Derived Advanced Biojet Fuels Using Different Generation Feedstocks: A Review

Abstract: As the fastest mode of transport, the aircraft is a major driver for globalization and economic growth. The development of alternative advanced liquid fuels is critical to sustainable development within the sector. Such fuels should be compatible with existing infrastructure and derived from second generation feedstocks to avoid competition with food markets. With properties similar to petroleum based fuels, isoprenoid derived compounds such as limonene, bisabolane, farnesane, and pinene dimers are of increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 117 publications
0
25
0
Order By: Relevance
“…In order to build Synechococcus a platform for pinene production, we need to integrate an exogenous pinene synthase into the genome of Synechococcus to convert GPP into αor β-pinene with high fidelity. Although both pinene isomers can be found in turpentine (Behr and Johnen, 2009), the β-pinene isomer is considered preferable for higher economic value (Sarria et al, 2014) and dimerization efficiency (Walls and Rios-Solis, 2020). Thus, the AgPS gene was selected to produce pinene with more proportion of β-pinene (Bohlmann et al, 1997) and had shown the highest activity for pinene synthesis in E. coli among the high-fidelity pinene synthases (Sarria et al, 2014).…”
Section: Determination Of Candidate Ps Genesmentioning
confidence: 99%
“…In order to build Synechococcus a platform for pinene production, we need to integrate an exogenous pinene synthase into the genome of Synechococcus to convert GPP into αor β-pinene with high fidelity. Although both pinene isomers can be found in turpentine (Behr and Johnen, 2009), the β-pinene isomer is considered preferable for higher economic value (Sarria et al, 2014) and dimerization efficiency (Walls and Rios-Solis, 2020). Thus, the AgPS gene was selected to produce pinene with more proportion of β-pinene (Bohlmann et al, 1997) and had shown the highest activity for pinene synthesis in E. coli among the high-fidelity pinene synthases (Sarria et al, 2014).…”
Section: Determination Of Candidate Ps Genesmentioning
confidence: 99%
“…Terpenoid hydrocarbons are suitable candidates for engineering advanced biofuels due to the branches and rings found in their hydrocarbon chains. The production of C 15 bisabolane has been performed in S. cerevisiae and E. coli [ 129 ]; that of limonene and oxidosqualene in Y. lipolytica [ 130 ]; farnesane [ 131 , 132 ] a replacement jet-fuel in E. coli ; and the tricyclic sesquiterpenes epi-isozizaene and pentalenene in E. coli , and α-isocomene in S. cerevisiae [ 133 ]. While the number of possible terpenoids is vast and represents a daunting bottleneck for further development, recent developments in AI and machine-guided genomic mining hold promise for more rapid identification and testing of possible biosynthetic pathways [ 134 ], thereby accelerating and streamlining the biosynthesis of novel biofuels.…”
Section: Engineering Microbial Metabolisms For Advanced Biofuelsmentioning
confidence: 99%
“…[15][16][17] Cyclic monoterpenes are an important class of bio-based cycloalkenes that can be derived from turpentine or produced via fermentation of biomass sugars. [18][19][20] Simple hydrogenation of these feedstocks can generate monocyclic and bicyclic hydrocarbons, 4 while chemoselective hydrogenation can afford bicyclic alkanes containing ring-strained cyclopropane groups. 21 The densities and volumetric NHOCs of terpenes can be further enhanced through cyclopropanation reactions.…”
Section: Introductionmentioning
confidence: 99%